Zalety i ograniczenia oceny efektywności kształcenia w kontekście reformy systemu informacji oświatowej - Bednarek, Piotr (The Advantages and Limitations of Performance Measurement Usage in Relation to Educational Information System Reform, 2005)
In a few countries of the world education system reforms were introduced, which make schools accountable for performance by obligation to include in schools annual reports performance information. This fact was an inspiration to question the scope of education information system reform in Poland. This paper attempts to find the answer to the question of the role and scope of educational reporting. On the one hand, there are some advantages about performance measurement usage presented. On the other hand, some limitations of performance measurement in schools are discussed on the basis of the previous research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 318-329